In vitro and in silico Analysis Protosappanin B Exerts Anti-Tumor Activity on Breast Cancer Cells via Activating Pro-Apoptotic Caspase Enzymes - Zhang, Xia; Deng, Shuangnian (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Breast cancer is the most common cancer and the second leading cause of cancer-associated mortality in women globally. Breast cancer can metastasize or recur because of drug resistance and toxicity. Objectives: The present work focuses on assessing the impact of in vitro and in silico analysis Protosappanin B on the growth and apoptosis of MDA-MB-231 cells. Materials and Methods: The effect of different concentrations of Protosappanin B on the MDA-MB-231 cells was investigated using the WST-1 assay. The Protosappanin B was assessed by analyzing the Lactate Dehydrogenase (LDH) amount that leaked into the growth medium. The analysis of apoptotic cells was done by using the dual staining method. The activities of the pro-apoptotic caspase-3, -8, and -9 enzymes in the cells were examined using respective assay kits and in silico Molecular docking studies. Results: The WST-1 assay results demonstrated that the Protosappanin B treatment at different dosages effectively inhibited MDA-MB-231 cell viability. The Protosappanin B effectively increased the LDH activity. The dual staining assay confirmed that Protosappanin B induced apoptosis in MDA-MB-231 cells. The activities of the caspase-3, 8, and -9 enzymes were remarkably elevated in the MDA-MB-231 cells after Protosappanin B treatment. Conclusion: The present study showed that Protosappanin B inhibits the viability of MDA-MB-231 cells and triggers their apoptosis via activating the pro-apoptotic caspase enzymes. Additionally, we confirmed the interactions of Protosappanin B with caspase enzymes through the molecular docking analysis. The computational study revealed that there are interactions between the Protosappanin B and caspase enzymes such as caspase-3 (-5.9 kcal/ mol; RMSD = 1.762 Å), caspase-8 (-5.9 kcal/mol; RMSD = 2.805 Å), and caspase-9 (-6.4 kcal/mol; RMSD = 1.731 Å). Overall, the results from the in vitro and in silico analysis strongly described that Protosappanin B induced the caspase-3, -8, and -9 and increased the apoptosis which reduced the cell proliferation of MDA-MB-231 cells. These findings clearly show the anticancer activity of Protosappanin B against breast cancer. The study involves nursing care for laboratory animals, including ethical approval, health screening, tumor induction, administration of Protosappanin B, pain management, hydration, nutrition, and housing. Data collection involves accurate record-keeping, statistical analysis, and post-study care. Key nursing interventions include vigilant monitoring, ethical treatment, supportive care, and accurate data collection.
Keywords: Protosappanin B; Caspases; Apoptosis; Breast cancer; Molecular docking